Taxonomic value of leaf anatomical characteristics of Coelostegia benth. and Ceiba pentandra Gaertn. (Bombacaceae) - S.N. Solihani,; T. Noraini,; A.R. Ruzi,; R.C.K Chung, (Universiti Kebangsaan Malaysia, 2010)
A comparative leaf anatomy was undertaken on some Coelostegia species (C.griffithii, C. borneensis and C. chartacea) and also Ceiba pentandra Gaertn. (Bombacaceae) as an outgroup species. The study includes transverse section of laminas and margins using sliding microtome. Leaf clearing was made using Basic Fuchsin in 10 % of KOH. The presence of mucilage cell, types of trichomes, types of laminar venation, presence of schlerenchyma cells and druses are common in all species studied. All Coelostegia species studied, have a unique characteristic in which solitary crystal is present exactly on above vascular bundles touching the adaxial epidermal and forms a structure-like girder. Coelostegia species can be distinguished by the margin outline, types of venation and in the presence or absence of trichomes. This study also showed that there were seven characters that can be used to differentiate between Coelostegia and Ceiba pentandra. The characters were swollen tracheid on the leaf laminar venation, pattern of vascular bundle in the petiole and midrib, the presence and types of crystal, the presence and types of trichomes, mucilagenous canals, hypodermis, collenchyma and schlerenchyma in the medullary vascular bundle in the petiole and in the leaf lamina. This study showed that the combination of anatomical characteristics has taxonomic value that can be useful for distinguishing species.